Oxygenated copper vanadium selenide composite nanostructures as a cathode material for zinc-ion batteries with high stability up to 10 000 cycles. Issue 8 (31st January 2023) - Narsimulu, D.; Krishna, B. N. Vamsi; Shanthappa, R.; Yu, Jae Su
Abstract : The oxygenated copper vanadium selenide composite electrode material as a cathode for aqueous zinc-ion batteries exhibits high capacity with ultra-long cycling life. Abstract : The development of aqueous zinc-ion batteries (AZiBs) towards practical implementations is hampered by unsuitable host cathode materials. Herein, we reported a high-capacity, stable, and long-cycle-life (10 000 cycles) oxygenated copper vanadium selenide composite material (Cu0.59 V2 O5 /Cu0.828 V2 O5 @Cu1.8 Se1 /Cu3 Se2, denoted as O–CuVSe) as a cathode for AZiBs. The newly constructed O–CuVSe composite cathode can be operated in the wide potential window of 0.4–2.0 V, exhibiting a high specific capacity of 154 mA h g −1 at 0.2 A g −1 over 100 cycles. Interestingly, the O–CuVSe composite cathode delivered excellent specific capacities of 117 and 101.4 mA h g −1 over 1000 cycles at 1 and 2 A g −1, respectively. Even at a high current density of 5 A g −1, the cathode delivered a high reversible capacity of 74.5 mA h g −1 over an ultra-long cycling life of 10 000 cycles with no obvious capacity fading. Apart from this, the cathode exhibited excellent rate capability at different current densities. The superior electrochemical properties originate from the synergistic effects between the oxygen vacancy engineering and interlayer doping of Cu ions to increase the structural stability during the cycling, enhancing the electron/ion transport kinetics. Moreover, the Zn 2+ storage mechanism in the Zn/O–CuVSe aqueous rechargeable battery was explored. This study provides a new opportunity for the fabrication of different kinds of a new class of cathode materials for high-voltage and high-capacity AZiBs and other energy storage devices.